Elections to the Chamber of Deputies in 2017 as a result of political changes in the Czech Republic - Czyżniewski, Marcin (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
Elections to the Chamber of Deputies of the Parliament of the Czech Republic, held on October 20 and 21, 2017, brought about the deepest change in the political system in that country. The composition of the Chamber, in comparison with the previous elections, changed distinctly, the potent parties had weakened and new parties succeeded. The new parties in the Chamber do not represent the traditional model of a political party, they do not bring new ideas and they do not grow out of the old ideological systems. They are populist parties that use and evoke social emotions and offering simple solutions, which are referred to as bussines-firm parties. The author emphasizes that the changes made in 2017, although very deep, are a natural consequence of trends visible earlier, at least since 2010 elections.